The Effect of Differentiated Learning Assisted by Learning Videos on the Outcomes of Science Learning in Grade IV of State Elementary School 131 Palembang - Muhammad Aziz Tanjung; Rury Rizhardi; Noviati Noviati (Universitas Muhammadiyah Enrekang, 2025)
The research problem in this study is as follows: Does Differentiated Instruction Assisted by Learning Videos Influence the Learning Outcomes of Science and Social Studies (IPAS) among 4th Grade Students at SD Negeri 131 Palembang?. This research aims to determine whether the application of Differentiated Instruction Assisted by Learning Videos has an effect on the learning outcomes of 4th grade students at SD Negeri 45 Palembang. The research method used in this study is a quantitative method. This study employed three data collection techniques: observation, tests, and documentation. Based on the research conducted by the researcher, the following conclusions can be drawn: 1) To determine whether there is a significant effect on learning outcomes after the implementation of Differentiated Instruction assisted by learning videos, a test consisting of 10 multiple-choice questions was administered to 4th grade students. The use of one class showed that after the application of differentiated instruction assisted by videos, students’ learning outcomes improved. The average pretest score was 64.23 (categorized as good), while the average posttest score was 83.57. These results indicate that the use of differentiated instruction assisted by learning videos positively influences student learning outcomes. 2) The hypothesis test results in this study show that the Paired Sample T-Test yielded a significance value of 0.00. Since this value is less than 0.05, the alternative hypothesis (Ha) is accepted and the null hypothesis (Ho) is rejected. Therefore, the hypothesis of this study is